Rectal indomethacin alone versus indomethacin and prophylactic pancreatic stent placement for preventing pancreatitis after ERCP: study protocol for a randomized controlled trial - Elmunzer, B. Joseph (Trials, 2016)
BACKGROUND: The combination of prophylactic pancreatic stent placement (PSP) – a temporary plastic stent placed in the pancreatic duct – and rectal non-steroidal anti-inflammatory drugs (NSAIDs) is recommended for preventing post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) in high-risk cases. Preliminary data, however, suggest that PSP may be unnecessary if rectal NSAIDs are administered. Given the costs and potential risks of PSP, we aim to determine whether rectal indomethacin obviates the need for pancreatic stent placement in patients undergoing high-risk ERCP. METHODS/DESIGN: The SVI (Stent vs. Indomethacin) trial is a comparative effectiveness, multicenter, randomized, double-blind, non-inferiority study of rectal indomethacin alone versus the combination of rectal indomethacin and PSP for preventing PEP in high-risk cases. One thousand four hundred and thirty subjects undergoing high-risk ERCP, in whom PSP is planned solely for PEP prevention, will be randomized to indomethacin alone or combination therapy. Those who are aware of study group assignment, including the endoscopist, will not be involved in the post-procedure care of the patient for at least 48 hours. Subjects will be assessed for PEP and its severity by a panel of independent and blinded adjudicators. Indomethacin alone will be declared non-inferior to combination therapy if the two-sided 95 % upper confidence bound of the treatment difference is less than 5 % between the two groups. Biological specimens will be obtained from trial participants and centrally banked. DISCUSSION: The SVI trial is designed to determine whether PSP remains necessary in the era of NSAIDs pharmacoprevention. The associated bio-repository will establish the groundwork for important scientific breakthrough. TRIAL REGISTRATION: NCT02476279, registered June 2015.